2019
DOI: 10.1111/jwas.12621
|View full text |Cite
|
Sign up to set email alerts
|

Integrated transcriptome provides resources and insights into the adaptive evolution of colonized brown trout (Salmo trutta fario) in the Tibetan Plateau

Abstract: The Tibetan Plateau is the world's largest plateau that is characterized by low temperature, low oxygen, and strong ultraviolet radiation. Colonized species that invade the plateau must change their characteristics to adapt to the harsh environment. However, research on the adaptation of introduced species on plateaus is limited. In this study, brown trout (Salmo trutta fario) was studied as a colonized species of the Tibetan Plateau, and a de novo transcriptome assembly was conducted to explore the genetic ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Hypoxia in the river system can be assumed to increase with elevation from sea level, resulting from a lower barometric pressure causing a decrease in oxygen levels. Distance from river mouth was very strongly correlated with elevation, and therefore candidate blocks associated with it may include particularly relevant candidate genes involved in altitude and hypoxia adaptation, such as the major regulators of hypoxia responses hif1a and eif5 (Braz-Mota & Almeida-Val, 2021;Tariq, Ito, Ishfaq, Bradshaw, & Yoshida, 2016), and rock2 (Chen et al, 2020).…”
Section: Functional Relevance Of Identified Candidate Genesmentioning
confidence: 99%
“…Hypoxia in the river system can be assumed to increase with elevation from sea level, resulting from a lower barometric pressure causing a decrease in oxygen levels. Distance from river mouth was very strongly correlated with elevation, and therefore candidate blocks associated with it may include particularly relevant candidate genes involved in altitude and hypoxia adaptation, such as the major regulators of hypoxia responses hif1a and eif5 (Braz-Mota & Almeida-Val, 2021;Tariq, Ito, Ishfaq, Bradshaw, & Yoshida, 2016), and rock2 (Chen et al, 2020).…”
Section: Functional Relevance Of Identified Candidate Genesmentioning
confidence: 99%
“…56,64 In comparison with other species of salmonids, transcriptome analysis indicated that Tibetan brown trout contains 129 positively selected genes and 126 species-specific gene families showing strong adaptability to high altitude, for example, genes related to energy metabolism, cardiovascular development, ammonium transport and DNA damage and repair. 90 Brown trout is now regarded as a locally naturalized species in Yadong, Tibet, and was even listed as a second-class key aquatic wild animal under protection in Tibet in 1992 (http://www.xizang.gov.cn/zwgk/xxfb/fgwj/ 201902/t20190223_61719.html). As one of the major economic fish species in Tibet, brown trout aquaculture is an important economic resource for local residents.…”
Section: The Outcome Of Non-native Fish Species In Chinamentioning
confidence: 99%
“…This species evolved some unique morphological, physiological and genetic characteristics that can be well adapted to the extreme environment of strong ultraviolet radiation and low temperature in the Yadong River, 88,89 and developed a relatively stable population (as a subspecies S. trutta fario ) 56,64 . In comparison with other species of salmonids, transcriptome analysis indicated that Tibetan brown trout contains 129 positively selected genes and 126 species‐specific gene families showing strong adaptability to high altitude, for example, genes related to energy metabolism, cardiovascular development, ammonium transport and DNA damage and repair 90 . Brown trout is now regarded as a locally naturalized species in Yadong, Tibet, and was even listed as a second‐class key aquatic wild animal under protection in Tibet in 1992 (http://www.xizang.gov.cn/zwgk/xxfb/fgwj/201902/t20190223_61719.html).…”
Section: Representative Fish Species Introduced For Aquaculturementioning
confidence: 99%
“…Previous studies have mainly focused on the high-altitude adaptability of plateau species, but little is known about the reasons why plain species cannot adapt to the plateau, because it is not clear which plateau stress factors play a major role (Cao et al, 2008;Yang et al, 2015;Xu et al, 2016;Chen et al, 2020). Under such unclear conditions, it may cause some studies to blindly select plain control species.…”
Section: Introductionmentioning
confidence: 99%